Implementation of corporate social responsibility in the process of strategic management - Korenyev, Е. (Національний університет "Львівська політехніка", 2013)
In the article modern approaches to the definition of the place of corporate social responsibility in the system of strategic management of an enterprise are analyzed. The conclusion about the priority role of the integrated approach to formation of business strategy as a tool of realization of the interests of stakeholders is drawn.
Keywords: corporate social responsibility; integrated approach; strategic management; strategy; stakeholders